Research on Control Strategy of Variable Frequency Starting System for Diesel-engine of AC Diesel Locomotive - 张朝阳; 许峻峰; 刘雄 (Kongzhi Yu Xinxi Jishu)
It proposed a vector control method, following which approximate unit power factor is got, based on the rotor flux oriention for the synchronous machine. The method was employed to control the excitation synchronous generator used in the starting system for dieselengine. The results of experiment show that the performance of the proposed control scheme is good.